Submicron particle dynamics for different surfaces under quiescent and turbulent conditions. (March 2017) - Vohra, Karn; Ghosh, Kunal; Tripathi, S.N.; Thangamani, I.; Goyal, P.; Dutta, Anu; Verma, V.
Abstract: Experiments were conducted using CsI aerosols in a small scale test chamber to simulate behaviour of aerosols in the containment of a nuclear reactor. The primary focus of the study was on submicron particles (14.3 nm–697.8 nm) due to their hazardous effect on human health. Different wall surfaces, viz., plexiglass, concrete and sandpaper were chosen to study the effect of surface roughness on dry deposition velocity under both quiescent and turbulent conditions. An analytical approach to calculate dry deposition velocity of submicron particles for rough surfaces has been proposed with an improvement in the existing parameterization for shift in the velocity boundary layer. The predicted deposition velocity with the improved parameterization was found to have better agreement with published measured data of Lai and Nazaroff (2005) compared to the existing parameterizations (Wood, 1981; Zhao and Wu, 2006b). There was a significant reduction in root mean square error (RMSE) between predicted, using the improved parameterization and measured deposition velocity (upto 100%) compared to earlier ones. The new analytical deposition approach was coupled with volume conserving semi-implicit coagulation model. This aerosol dynamic model was evaluated against explicit particle size distribution for the first time for rough surfaces. Normalized RMSE between simulated and measured particle size distribution varied in the range of 2%–20% at different instances. The model seems to closely predict submicron particle behaviour in indoor environment. Highlights: Modeling both coagulation and deposition to predict aerosol behavior accurately. Both coagulation and deposition are significant for submicron particles. Surface roughness and turbulence have a cumulative effect in increasing deposition. Increasing turbulence helps reduce aerosol peak concentration faster.